Caracterização físico-química de componentes do látex de espécies de Apocynaceae - Freitas, Larissa Barbosa Nogueira (2024)
The plant species Calotropis procera, Plumeria pudica and Himatanthus drasticus have a cellular system formed by specialized cells, called laticifers. In addition to the variety of metabolites produced in these cells, rubber particles (RPs) are formed, which remain suspended in the latex. These particles add high commercial value to the latex from Hevea brasiliensis, which has been, to moment, the only source of natural rubber (NR) for the industrial sector. NRs are also produced from the latices of C. procera, P. pudica and H. drasticus, however, there are no published studies. Very little is known about the structure (size, concentration, chemical composition and mechanical properties) of these RPs from plant species other than those from H. brasiliensis. Regarding the functions performed by these particles in plants, there is no consolidated data. This work evaluated intrinsic properties of the latices from C. procera, P. pudica and H. drasticus and their PBs. The latices were evaluated in diluted and whole forms. The zeta potential of these samples exhibited low negative values and even positive values, indicating low colloidal stability in the conditions tested. Rheological studies indicated adaptations against small herbivores and for wound healing in the plant. AFM (Atomic Force Microscopy) and SEM (Scanning Electron Microscopy) analyzes identified SRPs (RPs with a diameter equal to or less than 0.4 µm) and LRPs (RPs with a diameter equal to or greater than .5 µm) in the latices from C. procera, P. pudica and H. drasticus. The identification of polyisoprene molecules in the latices was confirmed by infrared and Raman spectroscopy. Furthermore, throughout this work, crystals were observed in the latex of P. pudica, which were identified as calcium malonate crystals. A comparative analysis of these crystals was carried out with another species of the genus Plumeria, where crystals with a carbon ring in their composition were identified. This work provides new possibilities for research into new plant species that are sources of NR. For the first time, NR and RP obtained from the latices of C. procera, P. pudica and H. drasticus were evaluated. It was also the first report of calcium malonate crystals and carbon-ring calcium crystals in plant latex.